The 2015 American Thyroid Association guidelines and trends in hemithyroidectomy utilization for pediatric thyroid cancer. Issue 8 (21st May 2022) - Stein, Eli; Raval, Mehul V.; Hazkani, Inbal; Reiter, Audra; Josefson, Jami L.; Samis, Jill H.; Rastatter, Jeffrey C.
Abstract: Background: In 2015, the American Thyroid Association (ATA) released its inaugural recommendations for the management of thyroid cancer in children. We aim to evaluate whether there has been a change in hemithyroidectomy utilization for pediatric differentiated thyroid cancer, and the association between those changes and the release of the ATA guidelines. Methods: The National Cancer Database was queried and identified 4776 patients ≤18 years old with differentiated thyroid cancer. Causal impact time‐series analysis and logistic analysis were utilized to assess factors associated with use of hemithyroidectomy. Results: Post‐2015 hemithyroidectomy rate was greater than predicted based on preguideline trends (predicted: 8.4%, actual: 12.6%, p = 0.001). In logistic analysis of factors associated with hemithyroidectomy use, we find that Papillary histology, tumor size >1 cm, nodal examination, and positive nodes were associated with lower rate of hemithyroidectomy (OR: 0.23, 0.51, 0.62, and 0.18, respectively). Conclusion: There has been a significant increase in hemithyroidectomy utilization for pediatric differentiated thyroid cancer.